IT SERVICE MANAGEMENT FOR BUSINESS PROCESS OF STAFF ARCHIVE DIGITALIZATION USING ITIL 3TH VERSION FRAMEWORK (CASE STUDY: BKPP OF SEMARANG CITY) - Yupie Kusumawati; Anggia Rizkika Hanin; Novita Kurnia Ningrum; Ibnu Utomo Wahyu Mulyono; Ajib Susanto; Karis Widyatmoko (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2024)
The role of archivist in an agency is as needed as in the Badan Kepegawaian, Pendidikan dan Pelatihan Kota Semarang (BKPP of semarang).Badan Kepegawaian, Pendidikan dan Pelatihan Kota Semarang currently has digitized archive services Employment is e-file service. The problem we found today is service the e-file is only used as a data archive and has not yet supported the business process resources. Another problem found on e-file services is not yet available service contact and lack of human resources. To support the business process then this research will design the management of it services on digitalization of employment archives. On this rre-design, e-file services will be linked to other IT services such as SISDM and E-Fungsional. This research uses the framework ITIL 3th Version domain service design with the sub domain service design package and service catalogue for document creation of the entire sequence of design. On this research there are also multiple support services like a service in contact, hours level services, risk identification, enhanced resources and structures the organization proposal so that current e-file services can support business processes digitalization of employment archives on the BKPP Kota Semarang